2018
DOI: 10.1111/pbr.12574
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci underlying soybean (Glycine max [L.] Merr.) seed weight including main, epistatic and QTL × environment effects in different regions of Northeast China

Abstract: Seed weight (SW) is the important soybean (Glycine max [L.] Merr.), yield component and also affected the quality of soybean‐derived foods. The aim of this study was to identify the quantitative trait loci (QTL) underlying SW through 112 recombinant inbred lines (RILs) derived from the cross between “Zhongdou27” (G. max, designated by its bigger seed size, 21.9 g/100 seeds) and “Jiunong 20” (G. max, smaller seed size, 17.5 g/100 seeds). Phenotypic data were collected from this RIL population after it was grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
(68 reference statements)
1
19
0
Order By: Relevance
“…The detection of at least two and up to seven major and several minor M-QTLs to condition SW in the crop indicates quantitative inheritance for the trait, consistent with findings in other legume crops 28,[51][52][53][54] . A genomic region on CcLG01 consistently showed highest PVE in three of the five mapping populations suggesting a common major genomic loci segregating in a wide range of genetic backgrounds, similar to reports in soybean 51 .…”
Section: Discussionsupporting
confidence: 84%
“…The detection of at least two and up to seven major and several minor M-QTLs to condition SW in the crop indicates quantitative inheritance for the trait, consistent with findings in other legume crops 28,[51][52][53][54] . A genomic region on CcLG01 consistently showed highest PVE in three of the five mapping populations suggesting a common major genomic loci segregating in a wide range of genetic backgrounds, similar to reports in soybean 51 .…”
Section: Discussionsupporting
confidence: 84%
“…In "QTL Hotspot D", QTLs related to seed maturity [33] and seed oil content [52] have formerly reported. Seed oil and protein content in soybeans have reported a significant correlation with seed size and shape [53], as seed oil and protein content represents a major component of soybean seeds, representing 38-42% and 18-22%, respectively; hence, these traits are directly related to seed sizes and shapes in soybeans [13]. Both seed size and shape are important yield component traits [54] and it has been reported that days to flowering and maturity is directly correlated to yield in soybeans [55,56], signifying the potential probability of common genic factors for these traits and also showing the necessity to promote further study for these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Specific soy-based food products made from soybean are also determined mainly by seed size and shape [9,10]. For example, for the production of fermented soybeans (natto) and sprouts, small-seeded cultivars are suitable, while for soymilk, green soybeans (edamame), boiled soybeans (nimame), and soybean curd (tofu), large-seeded varieties are used [11][12][13]. Additionally, these traits influence the germination ability and seedling vigor, and that, in turn, plays an essential role in determining the competitive strength of the seedlings for light, nutrient resources, and stress tolerance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The highly consistent marker loci across environments implied that these loci could be feasibly used in the marker‐assisted selection (MAS) program for 100‐SW in soybean (Mian et al., 1996). To map stable QTLs, we have conducted QTL analysis of 100‐SW under 16 environments in different regions of northeast of China (Wu et al, 2018). QTLs detected in multiple environments were stable enough for application to MAS.…”
Section: Discussionmentioning
confidence: 99%